Distributed control scheme for voltage regulation in smart grids - Sajadi, A.; Sebtahmadi, S.S.; Koniaka, M.; Biczel, P.; Mekhilef, Saad (2012)
The current uncertainty about oil and gas prices and their resources, and future energy concerns, smart grids lead to further development. In this paper, a two way communication-based distributed control for voltage regulation in smart grid is proposed. Moreover, 16-bus distribution feeders system is modeled by real time simulation in MATLAB/Simulink in order to evaluate the effectiveness of the proposed scheme. The results are evidence for capability of proposed system to regulate the voltage in smart distribution feeders.